An Analysis of Institutional Credit Pattern of Women Entrepreneurs - Ahsan, Mohammad Kamrul (American Journal of Trade and Policy, 2019)
This is an analytical paper. The aim of this paper is to find out which patterns of credit are frequently used by the women entrepreneurs. The result of this pepper will help the policy makers of financial institutions to decorate their schemes, especially for the women entrepreneurs. The researcher has used simple percentage analysis and graph to present the information with the help of Microsoft Excel 2007. The major findings of this paper are most of the women entrepreneurs are pleased to use institutional credit and they prefer private bank to get their credit. Most of them prefer to withdraw three hundred thousand to five hundred thousand taka as credit, interest rare nine percent to eleven percent, credit period two years to five years, installment monthly and the preferable monthly amount is five thousand to ten thousand taka.